Salt-Induced Membrane-Bound Conformation of the NAC Domain of α-Synuclein Leads to Structural Polymorphism of Amyloid Fibrils - Ryota Imaura; Koichi Matsuo (Biomolecules)
α-Synuclein (αS) interacts with lipid membranes in neurons to form amyloid fibrils that contribute to Parkinson’s disease, and its non-amyloid-β component domain is critical in the fibrillation. In this study, the salt (NaCl) effect on the membrane interaction and fibril formation of αS57–102 peptide (containing the non-amyloid-β component domain) was characterized at the molecular level because the αS57–102 fibrils exhibited structural polymorphism with two morphologies (thin and thick) in the presence of NaCl but showed one morphology (thin) in the absence of NaCl. The membrane-bound conformation (before fibrillation) of αS57–102 had two helical regions (first and second) on the membrane regardless of salt, but the length of the first region largely shortened when NaCl was present, exposing its hydrophobic area to the solvent. The exposed region induced two distinct pathways of fibril nucleation, depending on the molar ratios of free and membrane-bound αS57–102: one from the association of free αS57–102 with membrane-bound αS57–102 and the other from the assembly among membrane-bound αS57–102. The differences mainly affected the β-strand orientation and helical content within the fibril conformations, probably contributing to the thickness degree, leading to structural polymorphism.